Caractéristiques physiologiques au cours d`un exercice maximal chez des nageurs de surface élites - Boitel, G.; Vercruyssen, F.; Alberty, M.; Nesi, X.; Bourdon, L.; Brisswalter, J. (Science et motricité, 2012)
The objective of this study was to compare maximal physiological responses in both swimming pool and ergocycle in elite monofin-swimmers. Eight subjects performed in the swimming pool, a continuous incremental test but also an all-out 600 m test, and a maximal test on ergocycle in laboratory. Results indicate physiological responses significantly higher on ergocycle (P < 0.05) comparatively with monofin-swimming. However, no significant variation in these responses was observed between the monofin-swimming tests. The differences in physiological responses between the two modes of locomotion are mainly attributed to aquatic constraints and the specificity of global movement of the monofin-swimmer. The two monofin-swimming tests may be used in the real conditions to evaluate physiological responses.